Comparison Study Demosaicking of Bayer Color Filter Array - Naman, D. T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Image capturing in most still and  motion  digital  cameras  employs a charge  coupled  device  covered  with  a monolithic array  of color  filters such   that   each   pixel   samples  only   one  color   band.   Interpolation   is necessary   to  restore  the  missing  color  samples  in the  resulting mosaic, this process referred  to as demosaicking.This  paper   gives  an  overview   of  demosaicking,  presents  fewmethods   proposed   in  the  literature,   and  concludes   with  a  quantitative comparison of these methods for a set of images.